Epidemiology and Burden of Sepsis at Thailand’s Largest University-Based National Tertiary Referral Center during 2019 - Lalita Tancharoen (2022)
Data specific to the epidemiology and burden of sepsis in low-and middle-income countries are limited. This study aimed to determine the epidemiology and burden of adult patients with sepsis at Siriraj Hospital during 2019. Randomly selected adult patients who had blood cultures performed at our center during January–December 2019 were enrolled. A Quick Sepsis-related Organ Failure Assessment (qSOFA) score was used to determine the presence of sepsis. Demographic data and clinical outcome data were collected, and the annual incidence of sepsis or septic shock and death was estimated. Of the 987 subjects who had blood cultures performed, 798 had infections, 341 had sepsis, and 104 had septic shock. The prevalence of sepsis or septic shock was 34.9% among blood cultured patients, and 42.7% among those with infections. The prevalence of septic shock was 30.5% among subjects with sepsis. Approximately 63% of sepsis subjects were hospital-acquired infections. The factors independently associated with 28-day mortality in sepsis were receiving an immunosuppressive agent (adjusted odds ratio [aOR]: 2.37, 95% confidence interval [CI]: 1.27–4.45; p = 0.007), septic shock (aOR: 2.88, 95% CI: 1.71–4.87; p < 0.001), and proven infection (aOR: 2.88, 95% CI: 1.55–5.36; p = 0.001). Receiving appropriate, definitive antibiotic therapy (ABT) was independently associated with lower mortality in sepsis (aOR: 0.50, 95% CI: 0.27–0.93; p = 0.028) and septic shock subjects (aOR: 0.21, 95% CI: 0.06–0.72; p = 0.013). Achievement of mean arterial pressure (MAP) ≥ 65 mmHg (aOR: 0.09, 95% CI: 0.01–0.77; p = 0.028) and urine output ≥ 0.5 mL/kg/h (aOR: 0.15, 95% CI: 0.04–0.51; p = 0.006) were independently associated with lower mortality in septic shock patients. The incidence and mortality of sepsis remains high. Appropriate choice of definitive ABT and achievement of MAP and urine output goals may lower mortality in patients with sepsis or septic shock.